Population Fluctuations Oryctes rhinoceros L. Beetle in Plant Oil Palm (Elaeis guineensis Jacq.) Given Mulching Oil Palm Empty Bunch - Hafiz Fauzana; Agus Sutikno; Destia Salbiah (CROPSAVER, 2018)
Oil palm is a pre-eminent commodity in Indonesia, especially in Riau Province. The main pests that attack the oil palm is the pest of beetle Oryctes rhinoceros. The life cycle of pre-adult O. rhinoceros is on the ground, while the one that attacks the plant is the beetle stadia. The application of oil palm empty bunches (OPEB) to oil palm cultivation that functions as mulch and soil compost can improve the physical and biological properties of the soil, otherwise O. rhinoceros actually increases its population with OPEB application. The objective of this research is to know the population of O. rhinoceros in oil palm plantation given mulch of empty palm oil bunches. Research using survey method, observation done at PT. Adei Plantation & Industry. Observations made on the pradati with the size of the soil as a sample, to catch the adult beetles used ferotrap using pheromones as much as 5 ferotrap on 10 ha of land. Observations included the pre-adult population, the beetles population of O. rhinoceros, sex ratio, biomass, attack intensity. The results of research that has been done showsthat in the low adults population were the average of 8 tails per week, instar 2 most found was 15 tails. The population of beetles O. rhinoceros were the average of 23.8 tail / ferotrap / month. Population O. rhinoceros 1st week and 2nd, 3rd week decreased, lowest was at 4th week. The sex ratio of female and male beetles was 19.4: 4.4 or 4.54: 1. The intensity of O. rhinoceros attack was 11.72 ± 2.01% belonging to the category of minor attacks.Keywords: beetles O. rhinoceros, oil palm empty bunches, fluctuations, population.